2003
DOI: 10.1007/3-540-44945-0_3
|View full text |Cite
|
Sign up to set email alerts
|

Dunkl Operators: Theory and Applications

Abstract: Abstract. These lecture notes are intended as an introduction to the theory of rational Dunkl operators and the associated special functions, with an emphasis on positivity and asymptotics. We start with an outline of the general concepts: Dunkl operators, the intertwining operator, the Dunkl kernel and the Dunkl transform. We point out the connection with integrable particle systems of Calogero-MoserSutherland type, and discuss some systems of orthogonal polynomials associated with them. A major part is devot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
224
0
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 285 publications
(231 citation statements)
references
References 39 publications
1
224
0
6
Order By: Relevance
“…When |A ∩ B| = 1, the result holds by virtue of Lemma 4. Suppose that (20) holds at level n and consider the set B = B ∪{x} with x ∈ A and |A ∩ B| = n. Consider y ∈ A ∩ B; one can write Γ B as in (18). Since x, y ∈ A, Γ A commutes with Γ {x,y} and one can write {Γ A , Γ B } as in (19), the only difference with (19) being that x, y ∈ A.…”
Section: Proposition 2 ([19]mentioning
confidence: 99%
See 2 more Smart Citations
“…When |A ∩ B| = 1, the result holds by virtue of Lemma 4. Suppose that (20) holds at level n and consider the set B = B ∪{x} with x ∈ A and |A ∩ B| = n. Consider y ∈ A ∩ B; one can write Γ B as in (18). Since x, y ∈ A, Γ A commutes with Γ {x,y} and one can write {Γ A , Γ B } as in (19), the only difference with (19) being that x, y ∈ A.…”
Section: Proposition 2 ([19]mentioning
confidence: 99%
“…Since x, y ∈ A, Γ A commutes with Γ {x,y} and one can write {Γ A , Γ B } as in (19), the only difference with (19) being that x, y ∈ A. Upon applying the induction hypothesis, one finds (20) with B replaced by B after a straightforward calculation.…”
Section: Proposition 2 ([19]mentioning
confidence: 99%
See 1 more Smart Citation
“…In [5] it was shown that V exists and is one-to-one as a map on polynomials for any κ except for the set {− m 4 : m ∈ ‫,ގ‬ m 4 / ∈ ‫}ޚ‬ of singular values (for the case of B 2 ). Later Rösler [8] (see also [9]) proved that the functional f → Vf (x) is given by integration with respect to a positive measure, for each x ∈ ‫ޒ‬ 2 . Xu [10] found an intertwining transform for B 2 under restrictive conditions on degree and κ 1 , κ 2 .…”
Section: (1 + T) − (1 − T)) Dµ(t)mentioning
confidence: 99%
“…The book of Dunkl and Xu [6] is a reference for differential-difference operators, the intertwining operator and the kernel K(x, y) for any finite reflection group. Asymptotic formulae for the kernel are discussed in [9]. The author thanks the referee for useful remarks which helped improve the introduction and other details in the exposition.…”
Section: K(xw Y)mentioning
confidence: 99%